2022
DOI: 10.3390/v14112503
|View full text |Cite
|
Sign up to set email alerts
|

Tough Way In, Tough Way Out: The Complex Interplay of Host and Viral Factors in Nucleocytoplasmic Trafficking during HIV-1 Infection

Abstract: Human immunodeficiency virus-1 (HIV-1) is a retrovirus that integrates its reverse-transcribed genome as proviral DNA into the host genome to establish a successful infection. The viral genome integration requires safeguarding the subviral complexes, reverse transcription complex (RTC) and preintegration complex (PIC), in the cytosol from degradation, presumably effectively secured by the capsid surrounding these complexes. An intact capsid, however, is a large structure, which raises concerns about its transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 170 publications
0
2
0
Order By: Relevance
“…Since these T-cells are the regulators of the adaptive immune system, their depletion effectively weakens the immune system, leading to acquired immune deficiency syndrome (AIDS) (113). Several host factors have been shown to play an essential role in the HIV life cycle (114). PIN1 is one of these factors, enhancing HIV infection by being involved in three vital stages of the HIV replication cycle: Cell entry, reverse transcription and host genome integration (115,116).…”
Section: Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%
“…Since these T-cells are the regulators of the adaptive immune system, their depletion effectively weakens the immune system, leading to acquired immune deficiency syndrome (AIDS) (113). Several host factors have been shown to play an essential role in the HIV life cycle (114). PIN1 is one of these factors, enhancing HIV infection by being involved in three vital stages of the HIV replication cycle: Cell entry, reverse transcription and host genome integration (115,116).…”
Section: Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%
“…These steps include docking of the capsid (CA) onto NPC (NUP358), import of viral DNA (NUP153), integration of viral DNA into the host genome (NUP62, NUP98), and export of viral RNA (NUP98, NUP214, NUP62) ( 22 29 ). Furthermore, evidence shows that NUPs such as NUP358 and NUP153 are shown to be important for the HIV-1 integration site selection in the genome ( 26 , 30 , 31 ). Given their essential participation during HIV-1 replication, several proteomic studies have focused on and identified many NUPs that are dysregulated during HIV-1 infection ( 28 , 32 , 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that the core remains fully or mostly intact during nuclear entry, thereby ensuring completion of reverse transcription within the nucleus 3,4 . It is presently unclear how the core passes through the nuclear pore 68 while remaining intact. Docking of the HIV-1 core at the NPC and subsequent nuclear entry are effected by interactions between the capsid and cellular factors, including cyclophilin A, CPSF6, and nucleoporins (e.g.…”
mentioning
confidence: 99%